Self Presentation Media Sosial Instagram di Kalangan Milenial (Studi Kasus: Remaja di Desa Bakalanpule Kecamatan Tikung Kabupaten Lamongan) - Refansyah, Jaka (Jurnal PUBLIQUE, 2022)
Currently facing the millennial era, all social interactions are packaged in one medium, one of which is social media networking. Social media is now a stage where people show themselves to gain recognition and popularity. The purpose of this study is to determine self-presentation behavior in using Instagram social media among millennials, supporting and inhibiting factors in self-presentation and strategies used when using Instagram social media. The method used in this research is descriptive qualitative method and uses dramaturgy theory. Dramaturgy theory is a sociological perspective that focuses on management in everyday life and explores forms of social self, relationships, and social reality through the use of language and microanalytic interactions. The results of this study indicate the use of Self presentation in social media Instagram behavior is supported by the many features provided to build a self-image, then the supporting and inhibiting factors for expressing oneself on Instagram social media can be found on the person's profile page, and the self-presentation strategy is an attempt to deliberately form a certain impression or view with others to achieve a goal